2021
DOI: 10.1149/1945-7111/ac0df0
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Ion Insertion and Extraction on Non-Graphitizable Carbon with Closed Pore Structures

Abstract: We compared the insertion and extraction behaviors of lithium and sodium ions in non-graphitizable carbon with closed pore structures heat treated 2073 K and non-graphitizable carbon without heat treatment to investigate the elemental difference of the charge-transfer reactions of alkali metal ions from a kinetic viewpoint. The lithium system has smaller kinetic parameters for the insertion/extraction reactions such as charge transfer resistance and activation energy compared to those in the sodium system. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The results indicated that Li-ions had a lower migration impedance than Na-ions. 110 They believe that the rate performance of Li/Na-ion is determined by the energy barrier to cross the SEI's inorganic components. The lowest activation energy barriers calculated by density functional theory (DFT) show that Li-ion migration has a lower activation potential barrier than Na-ion migration.…”
Section: Lithium Chemistry Versus Sodium Chemistry-towards Hard Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that Li-ions had a lower migration impedance than Na-ions. 110 They believe that the rate performance of Li/Na-ion is determined by the energy barrier to cross the SEI's inorganic components. The lowest activation energy barriers calculated by density functional theory (DFT) show that Li-ion migration has a lower activation potential barrier than Na-ion migration.…”
Section: Lithium Chemistry Versus Sodium Chemistry-towards Hard Carbonmentioning
confidence: 99%
“…83 In contrast, Na-ions can be stored in the closed pores undebated, and improving capacity can be achieved by creating closed pores and adjusting the pore-entrance diameter. 110 The closed pore structure is ideal for the storage of Na-ions since it selectively allows Na-ions to pass through while excluding solvent molecules, thereby reducing the sites of electrolyte decomposition. However, the high HTT required for closed-pore formation can lead to over-graphitization, which must be taken into consideration.…”
Section: Lithium Chemistry Versus Sodium Chemistry-towards Hard Carbonmentioning
confidence: 99%
“…First, we focus on interfacial Li + transfer at transition metal oxides , as positive electrodes and Li 4 Ti 5 O 12 and graphite as negative electrodes. After that, we introduce a detailed analysis on a model interface, solid electrolyte/liquid electrolyte, to discuss the mechanism and rate-determining step. For graphite negative electrodes, the effects of electrolyte composition and solid electrolyte interphase (SEI) were also studied. In the latter part, we present strategies to accelerate the interfacial Li + transfer with an eye to electrolyte compositions, surface modifications, and types of battery reactions. Finally, we emphasize the importance of frequency factors (i.e., pre-exponential factors) as well as activation energies to dominate the kinetics of interfacial Li + transfer. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is noticeable that most of the battery electrodes utilized in CDI are mainly sodium-ion batteries or chloride-ion battery electrodes, owing to the direct relationship with the composition of the salt. Theoretically, the lithium-ion could be a more efficient charge carrier compared to these salt ions because of the smaller mass per unit of carried charge [ 23 , 24 , 25 , 26 ], and better desalination performance might be brought out. Based on this consideration, our group synthesized lithium-ion battery material LiMn 2 O 4 /C, which was further employed as the cathode in an HCDI device [ 27 ].…”
Section: Introductionmentioning
confidence: 99%